An examination of satisfaction towards online motorcycle taxis at different usage levels. Issue 3 (September 2020) - Suhartanto, Dwi; Dean, David; Gan, Christopher; Suwatno,; Chen, Brendan T.; Michael, Alouysius
Highlights: This study predicts behavioural intention towards online motorcycle taxi service. The drivers of behavioural intention differ across the service usage. Service quality of the taxi service consists of people, physical, and application. People factor has a crucial role in determining passenger satisfaction. Abstract: Despite the dramatic increase in online motorcycle taxis (OMTs) in many developing countries, empirical studies on passenger satisfaction toward OMTs have been overlooked. This study proposes a model of OMT passenger satisfaction where service quality and perceived value are determinants and behavioral intentions are the consequences, compared across three passenger segments based on service usage: light users, medium users, and heavy users. This research surveyed 500 OMT service users from Bandung city, Indonesia. The service quality factor analysis reveals three dimensions comprising people, physical, and application. The proposed satisfaction model is assessed by utilizing variance-based structural equation modelling, partial least squares. Examining the overall sample, this study confirms the association between service quality, perceived value, passenger satisfaction, and passenger' behavioral intention. Further, the results of this study disclose that the relationships between these constructs differ across service usage segments. The identified relationships highlight the crucial role the factor "people" plays in determining passenger satisfaction towards OMT services, especially for heavy users. The implications of these findings, for both theoretical development and managerial practices, were examined.